Fisheries and Fundamental Science: Donald Rawson's Studies of Lake Productivity - Bocking, Stephen (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1990)
ABSTRACTBetween 1930 and 1960 Donald Rawson was the leading limnologist in Western Canada. His work in the Fisheries Laboratory of the University of Saskatchewan between 1948 and 1960 is of particular interest. Through his surveys of lakes in his province he was able to contribute to development of theoretical concepts of lake productivity, while providing results useful to the provincial fisheries management agency.